Difficulties Facing Advanced Iraqi EFL Learners in Translating English Idioms into Arabic,and vice varsa - Hussein Abdulhussein (University of Mosul-college of Basic Education, 2021)
Abstract The present study is a linguistic investigation of equivalence above word level. It deals with the difficulties of non-equivalence posed in translating English idioms into Arabic and vice versa, and the methods used by 4" year students of English to find the suitable equivalent in the target language. The aim of this study is to examine the type of difficulty students at this level face while translating idioms and tries to suggest solutions and identify strategies that may help to limit or avoid these difficulties. In this respect, a test is  made up of twelve English idioms and ten Arabic ones are given to fourth level students to translate them. The results of the study are  show that there are potential problems in the process of translating idioms from English into Arabic  and vice versa. Furthermore, the findings show that the context of use helps a lot of students of English to guess the appropriate meaning of idioms. They also continue the hypothesis and reveal that, except word for word translation, students' use of other translation strategies is limited.